Acute hyperglycaemia enhances both vascular endothelial function and cardiac and skeletal muscle microvascular function in healthy humans. (2nd February 2021) - Horton, William B.; Jahn, Linda A.; Hartline, Lee M.; Aylor, Kevin W.; Patrie, James T.; Barrett, Eugene J.
Abstract : Key points: Multiple clinical studies report that acute hyperglycaemia (induced by mixed meal or oral glucose) decreases arterial vascular function in healthy humans. Feeding, however, impacts autonomic output, blood pressure, and insulin and incretin secretion, which may themselves alter vascular function. No prior studies have examined the effect of acute hyperglycaemia on both macro‐ and microvascular function while controlling plasma insulin concentrations. Macrovascular and microvascular functional responses to euglycaemia and hyperglycaemia were compared. Octreotide was infused throughout both protocols to prevent endogenous insulin release. Acute hyperglycaemia (induced by intravenous glucose) enhanced brachial artery flow‐mediated dilatation, increased skeletal muscle microvascular blood volume and flow, and expanded cardiac muscle microvascular blood volume. Compared to other published findings, the results suggest that vascular responses to acute hyperglycaemia differ based on the study population (i.e. normal weight vs . overweight/obese) and/or glucose delivery method (i.e. intravenous vs . oral glucose). Abstract: High glucose concentrations acutely provoke endothelial cell oxidative stress and are suggested to trigger diabetes‐related macro‐ and microvascular injury in humans. Multiple clinical studies report that acute hyperglycaemia (induced by mixed meal or oral glucose) decreases arterial vascular function in healthy humans. Feeding, however, impacts autonomic output, blood pressure, and insulin and incretin secretion, which may each independently alter vascular function and obscure the effect of acute hyperglycaemia per se . Surprisingly, no studies have examined the acute effects of intravenous glucose‐induced hyperglycaemia on both macro‐ and microvascular function while controlling plasma insulin concentrations. In this randomized study of healthy young adults, we compared macrovascular (i.e. brachial artery flow‐mediated dilatation, carotid‐femoral pulse wave velocity and post‐ischaemic brachial artery flow velocity) and microvascular (heart and skeletal muscle perfusion by contrast‐enhanced ultrasound) functional responses to euglycaemia and hyperglycaemia. Octreotide was infused throughout both protocols to prevent endogenous insulin release. Acute intravenous glucose‐induced hyperglycaemia enhanced brachial artery flow‐mediated dilatation ( P = 0.004), increased skeletal muscle microvascular blood volume and flow ( P = 0.001), and expanded cardiac muscle microvascular blood volume ( P = 0.014). No measure of vascular function changed during octreotide‐maintained euglycaemia. Our findings suggest that unlike meal‐provoked acute hyperglycaemia, 4 h of intravenous glucose‐induced hyperglycaemia enhances brachial artery flow‐mediated dilatation, provokes cardiac and skeletal muscle microvascular function, and does not impair aortic stiffness. Previous findings of acute large artery vascular dysfunction during oral glucose or mixed meal ingestion may be due to differences in study populations and meal‐induced humoral or neural factors beyond hyperglycaemia per se . (ClinicalTrials.gov number NCT03520569.)